Height of the first-person perspective affects the out-of-body experience illusion - Toi, Chiharu; Ishiguchi, Akira; Imaizumi, Shu (Frontiers in Virtual Reality, 2024)
Bodily illusions have been used to investigate one’s sense of self and body ownership. This study explored the effect of the height of the first-person perspective (1PP) on out-of-body experience (OBE) illusion in which participants see their backs through a head-mounted display, receive visuo-tactile stimulation, and gradually feel as if they are sitting behind themselves, experiencing a sensation similar to an OBE. We hypothesized that increasing or decreasing the height of the 1PP would induce the OBE illusion at all heights and that participants’ perceived own heights would adjust according to the 1PP height. We also predicted that the size and distance of external objects would vary according to the perceived height of one’s own body. The results revealed that the OBE illusion occurred at all 1PP heights and was stronger when the 1PP height was lower or higher than usual. Meanwhile, the participants’ perceived own heights, the sizes and distances of external objects did not change. These results suggest that manipulating the 1PP may affect the magnitude of the OBE illusion, but not the perception of the dimensions of the self or external objects. The height of 1PP may be one of the important factors in the bodily illusion.